Coding of Repetitive Transients by Auditory Cortex on Heschl's Gyrus - Brugge, John F. (American Physiological Society, 2009)
The capacity of auditory cortex on Heschl's gyrus (HG) to encode repetitive transients was studied in human patients undergoing surgical evaluation for medically intractable epilepsy. Multicontact depth electrodes were chronically implanted in gray matter of HG. Bilaterally presented stimuli were click trains varying in rate from 4 to 200 Hz. Averaged evoked potentials (AEPs) and event-related band power (ERBP), computed from responses at each of 14 recording sites, identified two auditory fields. A core field, which occupies posteromedial HG, was characterized by a robust polyphasic AEP on which could be superimposed a frequency following response (FFR). The FFR was prominent at click rates below ∼50 Hz, decreased rapidly as click rate was increased, but could reliably be detected at click rates as high as 200 Hz. These data are strikingly similar to those obtained by others in the monkey under essentially the same stimulus conditions, indicating that mechanisms underlying temporal processing in the auditory core may be highly conserved across primate species. ERBP, which reflects increases or decreases of both phase-locked and non–phase-locked power within given frequency bands, showed stimulus-related increases in gamma band frequencies as high as 250 Hz. The AEPs recorded in a belt field anterolateral to the core were typically of low amplitude, showing little or no evidence of short-latency waves or an FFR, even at the lowest click rates used. The non–phase-locked component of the response extracted from the ERBP showed a robust, long-latency response occurring here in response to the highest click rates in the series.